2003
DOI: 10.1080/15428110308984808
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds Produced During Irradiation of Mail

Abstract: In 2001, Bacillus anthracis spores were delivered through the United States postal system in a series of bioterrorist acts. Controls proposed for this threat included sanitization with high-energy electrons. Solid phase microextraction was used with gas chromatography/mass spectrometry for field sampling and analysis of volatile compounds apparently produced from polymeric materials such as cellulose and plastics, immediately following processing of mail at a commercial irradiation facility. Solid phase microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Widespread use of SPME in numerous fields has occurred since the method was first introduced in 1990, (11) including forensics, (12,13) biomedical applications, (14) environmental sampling, (15,16) historical document preservation, (17) sampling for worker health protection to determine unknown process reaction byproducts, (4) and for rapid sampling of chemical warfare agent compounds with relative safety. (18,19) …”
Section: High-performance Person-portable Gc-ms For Improved Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Widespread use of SPME in numerous fields has occurred since the method was first introduced in 1990, (11) including forensics, (12,13) biomedical applications, (14) environmental sampling, (15,16) historical document preservation, (17) sampling for worker health protection to determine unknown process reaction byproducts, (4) and for rapid sampling of chemical warfare agent compounds with relative safety. (18,19) …”
Section: High-performance Person-portable Gc-ms For Improved Exposurementioning
confidence: 99%
“…Incomplete or inaccurate ingredient lists (1,2) and the presence of unanticipated chemical reaction products (3,4) will potentially lead to inadequate exposure assessments unless work is performed to determine the actual chemicals present. A study completed within the past 10 years found several examples where disclosure of chemical constituents in three commercial products was legally required, but the respective material safety data sheet (MSDS) data did not list the correct hazardous ingredients.…”
Section: Introductionmentioning
confidence: 99%